Long-term PAH accumulation after bud break in L. leaves in a polluted environment - Alfani, a; Nicola, F; Maisto, G; Prati, M (Atmospheric Environment, 2005)
The dynamics of polycyclic aromatic hydrocarbon (PAH) concentrations in the leaves of Quercus ilex L. for 16 months after bud break (May 2001–September 2002) were studied at a polluted site in the urban area of Naples by comparison to the dynamics at a control site in the Vesuvius National Park. Twenty-seven PAHs were extracted by sonication and quantiﬁed by GC-MS. Total PAH concentrations in the leaves sampled at the urban site showed a considerable increase from bud break, with the highest values during the winter (about 3-fold greater than the initial value) and a subsequent decrease, unlike the control site. The control site exhibited PAH concentrations one order of magnitude lower than the urban site. At the urban site, the medium molecular weight PAHs, amounting to 72% of the total, appear responsible for the temporal trend, while the low and high molecular weight PAHs (respectively, 10% and 18%) exhibited only narrow variations over time. At the control site, the low, medium and high molecular weight PAHs contributed similarly to the total concentrations (32%, 31% and 37%, respectively); the low molecular weight PAHs showed the widest temporal variations. Carcinogenic PAHs showed a dynamic at the urban site comparable to that shown by the total PAHs. At the control site dibenzo(a,h)anthracene exhibited concentrations higher than at the urban site
Keywords: air contamination; carcinogenic pahs; pah dynamics; pah leaf accumulation; polycyclic aromatic hydrocarbons

Long-term PAH accumulation after bud break in L. leaves in a polluted environment - Alfani, a; Nicola, F.; Maisto, G.; Prati, M. (Atmospheric Environment, 2005)
The dynamics of polycyclic aromatic hydrocarbon (PAH) concentrations in the leaves of Quercus ilex L. for 16 months after bud break (May 2001–September 2002) were studied at a polluted site in the urban area of Naples by comparison to the dynamics at a control site in the Vesuvius National Park. Twenty-seven PAHs were extracted by sonication and quantiﬁed by GC-MS. Total PAH concentrations in the leaves sampled at the urban site showed a considerable increase from bud break, with the highest values during the winter (about 3-fold greater than the initial value) and a subsequent decrease, unlike the control site. The control site exhibited PAH concentrations one order of magnitude lower than the urban site. At the urban site, the medium molecular weight PAHs, amounting to 72% of the total, appear responsible for the temporal trend, while the low and high molecular weight PAHs (respectively, 10% and 18%) exhibited only narrow variations over time. At the control site, the low, medium and high molecular weight PAHs contributed similarly to the total concentrations (32%, 31% and 37%, respectively); the low molecular weight PAHs showed the widest temporal variations. Carcinogenic PAHs showed a dynamic at the urban site comparable to that shown by the total PAHs. At the control site dibenzo(a,h)anthracene exhibited concentrations higher than at the urban site
Keywords: air contamination; carcinogenic pahs; pah dynamics; pah leaf accumulation; polycyclic aromatic hydrocarbons

Temporal variations in PAH concentrations in Quercus ilex L. (holm oak) leaves in an urban area. - De Nicola, Flavia; Maisto, Giulia; Prati, Maria Vittoria; Alfani, Anna (Chemosphere, 2005)
Temporal variations of polycyclic aromatic hydrocarbon (PAH) concentrations in leaves of a Mediterranean evergreen oak, Quercus ilex L., were investigated in order to assess the suitability of this species to biomonitor PAH air contamination. Leaf samples were collected at six sites of the urban area of Naples (Italy) and at a control site in the Vesuvius National Park, in May and September 2001, and in January and May 2002. PAH extraction was conducted by sonication in dichloromethane-acetone and quantification by GC-MS. In winter, leaf total PAH concentrations showed, at all the urban sites, values 2-fold higher than in all the other samplings, reflecting the temporal trend reported for PAH air contamination in the Naples urban area. Moreover, leaf PAH concentrations showed, at all the urban sites, a decrease in May 2002 after the winter accumulation. At the control site leaf PAH concentrations showed lower values and smaller temporal variations than at the urban sites. The findings support the suitability of Q. ilex leaves to monitor temporal variations in PAH contamination. The highest winter concentrations of total PAHs were due to the medium molecular weight PAHs that increased with respect to both low and high molecular weight PAHs. The medium molecular weight PAHs showed the same temporal trend both at the urban and remote sites.
The following values have no corresponding Zotero field: accession-num: 16182861
Keywords: Aromatic; Aromatic: analysis; Cities; Environmental Monitoring; Environmental Pollutants; Environmental Pollutants: analysis; Italy; Mediterranean evergreen oak; Naples (Italy); PAH biomonitoring; pah leaf accumulation; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus: chemistry; Seasonal trend; Seasons; Time Factors

Temporal variations in PAH concentrations in Quercus ilex L. (holm oak) leaves in an urban area. - De Nicola, Flavia; Maisto, Giulia; Prati, Maria Vittoria; Alfani, Anna (Chemosphere, 2005)
Temporal variations of polycyclic aromatic hydrocarbon (PAH) concentrations in leaves of a Mediterranean evergreen oak, Quercus ilex L., were investigated in order to assess the suitability of this species to biomonitor PAH air contamination. Leaf samples were collected at six sites of the urban area of Naples (Italy) and at a control site in the Vesuvius National Park, in May and September 2001, and in January and May 2002. PAH extraction was conducted by sonication in dichloromethane-acetone and quantification by GC-MS. In winter, leaf total PAH concentrations showed, at all the urban sites, values 2-fold higher than in all the other samplings, reflecting the temporal trend reported for PAH air contamination in the Naples urban area. Moreover, leaf PAH concentrations showed, at all the urban sites, a decrease in May 2002 after the winter accumulation. At the control site leaf PAH concentrations showed lower values and smaller temporal variations than at the urban sites. The findings support the suitability of Q. ilex leaves to monitor temporal variations in PAH contamination. The highest winter concentrations of total PAHs were due to the medium molecular weight PAHs that increased with respect to both low and high molecular weight PAHs. The medium molecular weight PAHs showed the same temporal trend both at the urban and remote sites.
Keywords: Aromatic; Aromatic: analysis; Cities; Environmental Monitoring; Environmental Pollutants; Environmental Pollutants: analysis; Italy; Mediterranean evergreen oak; Naples (Italy); PAH biomonitoring; pah leaf accumulation; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus: chemistry; Seasonal trend; Seasons; Time Factors